2019
DOI: 10.18805/lr-4103
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic divergence in horsegram [Macrotyloma uniflorum (Lam) Verdc.] using quantitative traits

Abstract: Genetic relatedness studies using 12 quantitative traits on 252 genotypes in horsegram revealed wide spectrum of variability for yield components. The genotypes were grouped into 25 clusters based on estimates of D2 statistic. Cluster I had the largest number with 83 genotypes followed by cluster II (77 genotypes), cluster IV (33 genotypes) and cluster III (30 genotypes). On the contrary, 20 solitary clusters from cluster V to XXV were formed except cluster XIV (9 genotypes) which could be given priority for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…The magnitude of PCV varied substantially even among the former four traits. Similar results were reported by Priyanka et al (2021) and Visakh and Bindu (2022) in horse gram.…”
Section: Anovasupporting
confidence: 91%
“…The magnitude of PCV varied substantially even among the former four traits. Similar results were reported by Priyanka et al (2021) and Visakh and Bindu (2022) in horse gram.…”
Section: Anovasupporting
confidence: 91%
“…Priyanka et al (2021a;2021b) reported the success of induced mutagenesis in horse gram. The benefit of Mahalanobis 2 D statistic in estimating variability is well reported (Priyanka et al, 2021c). A negative relationship between yield and quality traits has been reported by Raatz (2018) Hertz: 2 MHz).…”
Section: Introductionmentioning
confidence: 77%
“…Sharma et al(2021) reported high heritability and genetic advance as per cent of mean for traits viz.,the number of primary branches per plant, the number of pods per plant, 100 seed weight and single plant yield in pigeonpea. The most appropriate method to estimate the diversity within any crop species is the D 2 statistics (Bhandari et al, 2017;Priyanka et al, 2021). The 68 pigeonpea genotypes were grouped into seven clusters.…”
Section: Resultsmentioning
confidence: 99%